Integrated Policy Approaches to Disaster Risk and Climate Change Governance: A Global Review of Institutional Strategies, Techniques, and Community Resilience - Himank Sharma (International Journal of Sustainability, 2025)
Climate change and disaster risks have emerged as interconnected threats that demand integrated and adaptive governance systems. While both domains, disaster risk management (DRM) and climate change adaptation (CCA), have independently evolved over time, their convergence remains a complex challenge for policymakers. This review explores the multidimensional integration of policies addressing disaster and climate risks, focusing on institutional coordination, community participation, and the use of innovative governance mechanisms. Drawing insights from diverse global contexts, including Pacific Island countries, South Africa, Colombia, Indonesia, and Myanmar, the study synthesizes key policy frameworks, governance barriers, and successful techniques. Using qualitative analysis and content review, we assess how collaborative governance, rapid needs assessment, educational planning, and informal settlement resilience contribute to sustainable risk management. The findings emphasize the importance of participatory, flexible, and context-sensitive approaches for achieving long-term resilience. Recommendations highlight the need for inclusive planning, systemic integration, and responsive institutional reform in risk-prone regions.
Keywords: Climate change adaptation; community participation; disaster risk management; governance; institutional coordination